IMPLEMENTATION OF POLICE INCREASE POLICY ON NARCOTIC USERS THROUGH REHABILITATION IN POLICE RESORT OF YOGYAKARTA CITY - Masnoto Masnoto; Eko Nurharyanto (Kajian Hasil Penelitian Hukum, 2017)
The invistigating officer Police Resort Of Yogyakarta City for dertemine penal polcy addicts narcotics of theft committed by narcotics on Law Number 35 Year 2009 articel 54 that is addicts narcotics and victims abuse narcotics obligatory medical rehabilitation and social rehabilitation, and implementation rehbilitation medical rehbilitation and social rehabilitation, to regulation with governance regulation by implemetation obligatory must be reported addict narcotic and victim abouse narcotics number 25 years 2011, TR Kabareskrim Polri no. 865 Year 2015 on the guidance of the formation of Integrated Assessment Team, Joint Regulation no. 1 of 2014 on Rehabilitation. Factors in determining a person may or may not be rehabilitated, Police Resort of Yogyakarta city implements two factors: first one is rehabilitation has fulfilled the legal process set forth in KUHAP. Both suspects are entitled to rehabilitation when a suspect has met the requirements of the terms of rehabilitation. Effectiveness in the implementation of rehabilitation can not suppress the awareness of narcotics, because as long as this policy is done since 2015, the increase of misuse in 2016 increased 3 fold, it can be seen from 20 suspects who get the rehabilitation policy of Police Investigator Yogyakarta.Keywords: Legal policy, abuse of narcotics, rehabilitation